Phylogenetic Analysis of the SQUAMOSA Promoter-Binding Protein-Like Genes in Four Ipomoea Species and Expression Profiling of the IbSPLs During Storage Root Development in Sweet Potato (Ipomoea batatas) - Sun, Haoyun; Mei, Jingzhao; Zhao, Weiwei; Hou, Wenqian; Zhang, Yang; Xu, Tao; Wu, Shaoyuan; Zhang, Lei (Frontiers in Plant Science, 2022)
As a major plant-speciﬁc transcription factor family, SPL genes play a crucial role in plant growth, development and stress tolerance. The SPL transcription factor family has been widely studied in various plant species; however, systematic studies on SPL genes in the genus Ipomoea are lacking. Here, we identified a total of 29, 27, 26, and 23 SPLs in Ipomoea batatas, Ipomoea trifida, Ipomoea triloba, and Ipomoea nil, respectively. Based on the phylogenetic analysis of SPL proteins from model plants, the Ipomoea SPLs were classified into eight clades, which included conserved gene structures, domain organizations and motif compositions. Moreover, segmental duplication, which is derived from the Ipomoea lineage-specific whole-genome triplication event, was speculated to have a predominant role in Ipomoea SPL expansion. Particularly, tandem duplication was primarily responsible for the expansion of SPL subclades IV-b and IV-c. Furthermore, 25 interspecific orthologous groups were identified in Ipomoea, rice, Arabidopsis, and tomato. These findings support the expansion of SPLs in Ipomoea genus, with most of the SPLs being evolutionarily conserved. Of the 105 Ipomoea SPLs, 69 were predicted to be the targets of miR156, with seven IbSPLs being further verified as targets using degradome-seq data. Using transcriptomic data from aboveground and underground sweet potato tissues, IbSPLs showed diverse expression patterns, including seven highly expressed IbSPLs in the underground tissues. Furthermore, the expression of 11 IbSPLs was validated using qRT-PCR, and two (IbSPL17/IbSPL28) showed significantly increased expression during root development. Additionally, the qRT-PCR analysis revealed that six IbSPLs were strongly induced in the roots under phytohormone treatments, particularly zeatin and abscisic acid. Finally, the transcriptomic data of storage roots from 88 sweet potato accessions were used for weighted gene co-expression network analysis, which revealed four IbSPLs (IbSPL16/IbSPL17/IbSPL21/IbSPL28) clusters with genes involved in ‘regulation of root morphogenesis’, ‘cell division’, ‘cytoskeleton organization’, and ‘plant-type cell wall organization or biogenesis’, indicating their potential role in storage root development. This study not only provides novel insights into the evolutionary and functional divergence of the SPLs in the genus Ipomoea but also lays a foundation for further elucidation of the potential functional roles of IbSPLs on storage root development.